D-Dimer Combined with Fibrinogen Predicts the Risk of Venous Thrombosis in Fracture Patients - Chaohui Lin; Yifan Chen; Bin Chen; Ke Zheng; Xiongbiao Luo; Fengfei Lin (Emergency Medicine International)
Objective. While D-dimer can successfully diagnose venous thrombosis due to its excellent negative predictive value (NPV), it cannot be used to detect venous thromboembolism (VTE) because of its low positive predictive value (PPV). This study aims to investigate if a combination of using D-dimer and fibrinogen can improve PPV in the VTE diagnosis. Methods. We retrospectively analyzed various data including D-dimer, fibrinogen, C-reactive protein, ultrasound, and others collected from 10775 traumatic fracture patients and categorized them into two groups of VTE and non-VTE. By comparing the difference between the two groups, we employ multiple logistic regression to find risk factors that are useful to detect VTE. The receiver operating characteristic (ROC) curve was used to evaluate the diagnostic yield of using fibrinogen, D-dimer, and their combination, respectively. Also, these data were classified into quartiles by patient age. We perform the same analysis on the quartiles and find if the patient’s age has an impact on diagnosing VTE. Results. The univariate analysis demonstrated that five factors of age, D-dimer, fibrinogen, C-reactive protein, and high-density lipoprotein cholesterol were significant to predict VTE. ROC showed that D-dimer was more useful than fibrinogen for the diagnosis of VTE, while the area under the curve (AUC) was 0.7296 for D-dimer and 0.5209 for fibrinogen. The cutoff point of D-dimer and fibrinogen was 424.89 ng/ml and 3.543 g/L, respectively. The specificity of fibrinogen was 0.777 which was better than D-dimer, while the sensitivity of fibrinogen was lower than that of D-dimer. Both PPV and NPV were similar in D-dimer and fibrinogen. The PPV of combining D-dimer and fibrinogen in ages Q3 (60 < age ≤ 70) and Q4 (age > 70) was better than using either D-dimer or fibrinogen. Conclusions. Fibrinogen is a promising strategy for the diagnosis of subclinical VTE and postoperative VTE. In particular, a combination of D-dimer and fibrinogen can improve the PPV to successfully diagnose VTE in traumatic fracture patients who are more than 60 years old. Levels of Evidence. This assay is a diagnostic test at level II.